Multiple Access Communications 6th International Workshop, MACOM 2013, Vilnius, Lithuania, December 16-17, 2013, Proceedings - Jonsson, Magnus; Vinel, Alexey; Bellalta, Boris; Ninoslav, Marina; Desislava, Dimitrova; Fiems, Dieter (Computer Communication Networks and Telecommunications, 2013)
This book constitutes the refereed proceedings of the 6th International Workshop on Multiple Access Communications, MACOM 2013, held in Vilnius, Lithuania, in December 2013. The 16 full papers presented were carefully reviewed and selected from various submissions. They describe the latest advancements in the field of multiple access communications with an emphasis on OFDM techniques, channel coding, spectrum management, medium access control protocols and different aspects of wireless access networks.